Analysis of the Rice-Orange Farming Pattern in Rainfed Land in Astambul District Banjar Regency - Zaini, Muhammad; Husaini, Muhammad; Lutfhi, Lutfhi (Asian Journal of Social and Humanities, 2025)
This study aims to analyze two main aspects related to the paddy–citrus farming system in Astambul District, Banjar Regency. First, it seeks to examine the production, costs, revenues, and income generated from the paddy–citrus farming system. Second, the study evaluates the financial feasibility of implementing this farming system on rainfed agricultural land. A survey method was employed, using a two-stage random sampling technique. In the first stage, three villages in Astambul District were randomly selected. In the second stage, 36 farmers were randomly chosen from a total population of 180 farmers across the three villages. The data were analyzed using descriptive statistics and Revenue Cost Ratio (RCR) analysis. The average production from the paddy–citrus farming system was 4.04 tons of paddy and 7.88 tons of citrus per farm. The average total cost incurred was IDR 17,695,620.84 per farm, consisting of explicit costs of IDR 15,644,622.62 and implicit costs of IDR 2,050,998.22 per farm. The average revenue was IDR 87,521,252.78 per farm. With an average explicit cost of IDR 15,644,622.62, the resulting average income was IDR 72,710,978.31 per farm. Based on the Revenue Cost Ratio (RCR) analysis, with an average revenue of IDR 87,521,252.78 and an average total cost of IDR 17,695,620.84 per farm, the RCR value was 5.15. This figure is significantly greater than 1, indicating that the paddy–citrus farming system is profitable and financially feasible. For every IDR 1 of cost incurred, a return of IDR 5.15 is generated.